PENGARUH PEMBERIAN SIT- UP EXERCISE DAN BICYCLE CRUNCH EXERCISE UNTUK PENURUNAN LINGKAR PERUT - Meiza Anniza (Poltekkes 'Aisyiyah Banten, 2022)
Background: Abdominal circumference is a method used to determine central obesity. Women were declared to have central obesity if the waist circumference was > 80 cm and men > 90 cm based on the WHO criteria for Asian adults. Central obesity is a state of excess fat that accumulates in the abdominal area. Central obesity can have a negative impact on health and increase the risk of death. Objective: To determine the effect of Sit up exercise and Bicycle Crunch exercise to decrease abdominal circumference using narrative review method. Methods: The method used in this research is Narrative Review by collecting 10 journals that match the inclusion and exclusion criteria. Results: From 10 journals using the Narrative Review method, 7 journals state that sit-ups are effective and 3 journals state that bicycle crunch exercise is effective in reducing abdominal circumference. Conclusion: There is an effect of sit up exercise and bicycle crunch exercise in reducing abdominal circumference.